The Effect of Lighting on Sleep Quality in The Elderly in Sidodadi Village - Hendrik Probo Sasongko; Febrika Devi Nanda (Lembaga Pengembangan Kinerja Dosen, 2025)
Sleep disorders in the elderly are a problem that can affect overall health. The lighting factor during sleep is thought to influence sleep quality through inhibiting melatonin production and disrupting circadian rhythms. This research used a cross-sectional design with a total sampling of 44 elderly respondents in Sidodadi Village, Banyuwangi. The independent variable is lighting (bright, dim, dark), while the dependent variable is sleep quality. Data analysis was carried out using the chi-square test. Most respondents slept in darkness (52.4%), and the majority had good sleep quality (83.3%). However, the results of the chi-square test showed that there was no significant relationship between lighting and sleep quality (p-value = 0.066). This research concludes that lighting does not have a statistically significant relationship with the sleep quality of the elderly in Sidodadi Village. Further research is needed to consider other variables that may influence sleep quality in older adults.